2017
DOI: 10.1177/0095327x17715650
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Stereotypes

Abstract: This study examines reader responses to opinion editorials about women in combat and contributes to the literature on women in the military by explaining how contests over sex–gender essentialism and diversity underlie public debates about individual rights and military effectiveness. Comments in favor of women’s ground combat exclusion use a logic of averages to promote essentialist thinking about men and women. They categorize women as inferior soldiers and argue that desegregation puts individual soldiers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…Review of debates focused on the feasibility of integration women into the armed services shows that the arguments of opponents of gender equality are concerned mainly women's physical and psychological inability for military service. Collins-Dogrul and Ulrich [10] examined reader responses to editorials opinion about women in combat. They concluded that the rationale for denying the feasibility of integration women into armed services is based on a logic of averages, which in everyday life usually reflects the recourse to traditional stereotypes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of debates focused on the feasibility of integration women into the armed services shows that the arguments of opponents of gender equality are concerned mainly women's physical and psychological inability for military service. Collins-Dogrul and Ulrich [10] examined reader responses to editorials opinion about women in combat. They concluded that the rationale for denying the feasibility of integration women into armed services is based on a logic of averages, which in everyday life usually reflects the recourse to traditional stereotypes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, supporters of integration suggest that granting to women the right to serve in ground combat will advance both equality and military readiness. Collins-Dogrul and Ulrich [10] argue that public comments about women's participation in hostilities provide an opportunity to explore gender stereotypes in society. Results of research carried out by Doan and Portillo [12] demonstrate that gender stereotypes often work against changes, especially when these changes have the potential to disrupt an organization's culture and standard operating procedures of a military organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, studies have found that the prevailing image of a soldier 1 remains masculine (Alchin et al, 2018;Boldry et al, 2001;Do & Samuels, 2021), and that soldiers can be socialized into sexist attitudes and behavior within the military (Gibbons & Rossi, 2022). Furthermore, integrating women into the military structurally does not automatically change these norms (Carreiras, 2006;Collins-Dogrul & Ulrich, 2018;Ette, 2013;Higate, 2003;King, 2015;Kvarving, 2019;Pendlebury, 2020;Welland, 2010). The persistence of the masculine normative ideal makes it difficult for individuals who are perceived or identify as feminine 2 to fully identify and become soldiers (Muhr & Sløk-Andersen, 2017;Reis & Menezes, 2020;Wilen & Heinecken, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…mm., no todos los Estados han logrado mejorar el estatus de las mujeres militares en la misma medida, y "las políticas de igualdad de oportunidades y diversidad no han tenido un éxito uniforme" (Ellner, 2015, p. 300). Aunque en 2013 el Secretario de Defensa de los Estados Unidos, Leon E. Panetta, eliminó la prohibición para las mujeres militares de servir en misiones de combate (Collins-Dogrul & Ulrich, 2018), y aunque, a partir del 2016, el 96,3 % de los Estados miembros de la otan tienen todos los roles militares abiertos para las mujeres (otan, 2016), otras experiencias han mostrado múltiples dificultades para su incorporación a entornos tradicionalmente masculinos como las ff. mm.…”
Section: Introductionunclassified